Risk Analysis of Fresh Lemuru Fish Supply Chain at Banyuwangi Port - Rizkina, Fitriana Dina; Fauzi, Nurul Fathiyah; Assadam, Ahib; Hapsari P. P., Tiara Aprilia; Ramad, Shinta Artamevia (Hasanuddin University, 2023)
The abundance of lemuru fishery products around Coastal Fisheries Port in Muncar has led to the growth of a processing industry cluster made from lemuru fish which produces canned fish (sardines, tuna), fish flour and oil as well as frozen fish around Muncar port. Factories or industries whose raw materials require a large amount of money to move materials that are easily damaged will tend to choose their industrial locations around sources of raw materials. This shows that Indonesian people are aware of the nutritional contribution of consuming fish. The amount of production and consumption of this fish is also influenced by the season and weather so that the supply of caught fish is uncertain but the demand for fish is always increasing. Apart from that, other risks are inaccurate knowledge of fish handling, the distribution of caught fish that takes too long affects the decrease in the quality of fresh caught fish and the selling price of caught fish. Flying fish at Muncar Fishery Port is very dependent on the fishing season, so the availability of supplies fluctuates. The purpose of this study was to identify the supply chain structure and supply chain risks for lemuru at Muncar Fishery Port, analyze the highest risk factors in the lemuru supply chain at Muncar Fishery Port at each tier of fishermen, collectors and traders and recommends supply chain risk mitigation for lemuru fish for each tier at the Muncar Fishery Port based on risk identification.